2020
DOI: 10.1093/molbev/msaa266
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Adaptations to Salinity Resist Gene Flow in the Evolution of Floridian Watersnakes

Abstract: The migration-selection balance often governs the evolution of lineages, and speciation with gene flow is now considered common across the tree of life. Ecological speciation is a process that can facilitate divergence despite gene flow due to strong selective pressures caused by ecological differences; however, the exact traits under selection are often unknown. The transition from freshwater to saltwater habitats provides strong selection targeting traits with osmoregulatory function. Several lineages of Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…In aquatic species, salinity is a common environmental stressor that can remarkably affect metabolism and osmotic regulation of various organisms (Vargas-Chacoff et al, 2015). Marine animals can maintain their most critical physiological functions through multiple molecular mechanisms when exposed to salinity stresses, despite that there are alterations in osmotic pressure and cytoplasmic composition in their cells (Rautsaw et al, 2020). In our study, the identified DAPs in C. robusta exposed to both low and high salinity stresses were significantly enriched in the pathways "posttranslational modifications (PTMs)," "cytoskeleton, " and "signal transduction, " suggesting the involvements of these pathways in the responses of stolon to salinity stress.…”
Section: Discussion Proteomic Response To Salinity Stressmentioning
confidence: 99%
“…In aquatic species, salinity is a common environmental stressor that can remarkably affect metabolism and osmotic regulation of various organisms (Vargas-Chacoff et al, 2015). Marine animals can maintain their most critical physiological functions through multiple molecular mechanisms when exposed to salinity stresses, despite that there are alterations in osmotic pressure and cytoplasmic composition in their cells (Rautsaw et al, 2020). In our study, the identified DAPs in C. robusta exposed to both low and high salinity stresses were significantly enriched in the pathways "posttranslational modifications (PTMs)," "cytoskeleton, " and "signal transduction, " suggesting the involvements of these pathways in the responses of stolon to salinity stress.…”
Section: Discussion Proteomic Response To Salinity Stressmentioning
confidence: 99%
“…It is possible now to determine which traits are involved in reproductive isolation by examining significant differences between taxa across their genomes and then relate those differing alleles to morphology (Han et al, 2017). For example, an intriguing recent study (Rautsaw et al, 2020) looked at genomic divergence between the Florida watersnakes Nerodia clarkii, occurring in high-salinity environments, and N. fasciata, in freshwater environments. They demonstrated that despite recurring historical and contemporary gene flow between these taxa, several key loci were responsible for ecological divergence in these environments.…”
Section: Reproductive Isolation and Hybrid Zonesmentioning
confidence: 99%
“…Dispersal (and its genetic consequence, gene flow) counter the potential for local adaptation. However, when selection is strong, it may overcome the homogenizing effects of gene flow, to the point of creating population structure and even occasionally resulting in speciation (Nosil 2008;Savolainen et al 2013;Arick et al 2020). Considering the strong environmental gradient encountered by Lessepsian migrants in the Suez Canal, genes under selection involved with osmoregulation have been found in the bluespotted cornetfish, a very successful Lessepsian migrant (Bernardi et al 2016).…”
Section: Natural Selection and Preadaptationsmentioning
confidence: 99%